2012
DOI: 10.1017/s0950268812000453
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence typing (MLST) analysis of 104Clostridium difficilestrains isolated from China

Abstract: SUMMARYThe phylogenetic and epidemic relationships of 104 clinical isolatesof Clostridium difficilefrom three hospitals of different geographical and population sources in China were investigated by multilocus sequence typing. Twenty-two sequence types (STs) were identified, four of which, ST117, ST118, ST119 and ST129, were novel. No geographically specific and host population-specific phylogenetic lineages were found and there was no correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
32
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 13 publications
8
32
2
Order By: Relevance
“…Yet, our previous study demonstrated significant genetic diversity in tcdA and tcdB, consistent with the results of toxinotyping based on the restriction fragment length polymorphism (RFLP)-PCR method (19,28). However, the simple classification of RFLP-PCR failed to explain more details about the epidemiological relevance and phylogenetic relationships between strains with different types of toxin genes, while the recently increased ST37 (RT017 [A Ϫ B ϩ ]) contribution (48%) for CDI cases and its epidemic potentiality in Asia (11,16) make it urgent to build a more finely described pattern to reveal the intrinsic epidemic characteristics. In the present study, we introduce a novel approach that is more discerning and accurate; for example, 13 ST35 and 11 ST2 strains were divided into 2 groups (A03B04 and A02B05 and A06B07 and A09B06, respectively).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Yet, our previous study demonstrated significant genetic diversity in tcdA and tcdB, consistent with the results of toxinotyping based on the restriction fragment length polymorphism (RFLP)-PCR method (19,28). However, the simple classification of RFLP-PCR failed to explain more details about the epidemiological relevance and phylogenetic relationships between strains with different types of toxin genes, while the recently increased ST37 (RT017 [A Ϫ B ϩ ]) contribution (48%) for CDI cases and its epidemic potentiality in Asia (11,16) make it urgent to build a more finely described pattern to reveal the intrinsic epidemic characteristics. In the present study, we introduce a novel approach that is more discerning and accurate; for example, 13 ST35 and 11 ST2 strains were divided into 2 groups (A03B04 and A02B05 and A06B07 and A09B06, respectively).…”
Section: Discussionsupporting
confidence: 71%
“…All 70 strains were characterized by the MLST method with seven housekeeping genes (21), and sequences were submitted to the Clostridium difficile multilocus sequence typing (MLST) database (http://pubmlst.org /cdifficile) to acquire a sequence type (ST). Thirty-five strains were part of the 104 strains used in our previous MLST study (16). A minimum spanning tree was also constructed to exhibit the population structure of Chinese strains using the categorical data for MLST via BioNumerics v4.0 software (Applied Maths BVBA, Belgium).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (7). Recently, multilocus sequence type (MLST) data have been published on isolates largely from Beijing, for which the dominant MLST type was found to be ST37, which the authors stated was representative of ribotype 017 (10). In contrast to mainland China, in Hong Kong C. difficile has been recognized for some time, the earliest report being from 1991 to 1993 in bone marrow transplant patients (11).…”
mentioning
confidence: 99%
“…Previous studies have reported ST-54, ST-35, and ST-37 as the top 3 prevalent genotypes in China (18). In addition, Zhou et al found ST-54 and ST-37 to be the prevalent genotypes in the Chinese city of Shanghai10.…”
Section: Discussionmentioning
confidence: 97%